Preparation method of multifunctional high-visibility fabric

By modifying polyester-cotton blended fabrics and using components such as fluorine-free waterproof and stain-proof finishing agents for single-side printing, combined with low-temperature ultraviolet curing technology, the problem of existing high-visibility fabrics lacking waterproof, anti-fouling and moisture-permeable functions in outdoor applications is solved, and the fabrics are well-waterproof, anti-fouling and moisture-permeable functions and high visibility are achieved.

CN119843483AActive Publication Date: 2025-04-18FUKE NEW MATERIALS (SHANGHAI) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510344462.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-18
Estimated Expiration
2045-03-21

AI Technical Summary

Technical Problem

The existing high-visibility fabrics lack waterproof, stain-proof and moisture-permeable functions in outdoor applications, resulting in insufficient comfort for the wearer.

Method used

By modifying the polyester-cotton blended fabric, and using slurries formed by components such as fluorine-free waterproof and anti-fouling finishing agent, pigment and persimmon paint for single-side printing, combined with low-temperature ultraviolet curing technology, high-visible fabrics with fluorescence performance, washing and durability are prepared.

Benefits of technology

It realizes the good waterproof, stain-proof and moisture-permeable function of the fabric, while maintaining high visibility and comfort, and is suitable for outdoor applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843483A_ABST
    Figure CN119843483A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a multifunctional high-visibility fabric, and belongs to the technical field of functional textiles. The preparation method comprises the following steps: adding water into sodium hydroxide, cellulose compound enzyme and a penetrant to prepare a modifier, dipping the cotton-polyester blended fabric in the modifier, washing to be neutral, and drying to obtain a modified fabric; the preparation method comprises the following steps: taking guar gum and nano silicon dioxide as monomers, adding acrylic acid, butyl acrylate, lauryl sodium sulfate and water, and stirring to obtain a monomer emulsion; adding an initiator into the monomer emulsion, reacting to obtain a polyacrylate emulsion, adding sodium dodecyl benzene sulfonate, an emulsifier and acryloyloxypropyl polyhedral oligomeric silsesquioxane, and reacting to obtain a finishing agent; according to the process, a relatively low temperature is used for achieving relatively good waterproof performance, the influence of high-temperature baking on the fluorescence performance and the hand feeling of the fabric is avoided, and energy is saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a method for preparing a multifunctional high-visibility fabric, and belongs to the technical field of functional textiles. Background Art

[0002] In recent years, with the development of science and technology and the improvement of people's consumption level, the market demand for functional and intelligent textile products has continued to grow, and the market demand for products such as comfort, health, and safety protection has increased. Among them, functional protective high-visibility clothing is made of eye-catching base materials and luminous or reflective materials. In extremely poor visibility conditions such as darkness, heavy rain, blizzards, sandstorms, and fog, it can not only significantly distinguish the wearer from the surrounding environment, but also serve as a warning to others to avoid accidents. It can be widely used in traffic police, road surveyors, sanitation workers, road administration and greening workers, as well as night running clothes, festivals and stage costumes. At present, there are many studies on high-visibility warning fabrics, but for outdoor application environments, waterproof, anti-fouling and breathable are very important for improving the comfort of the wearer. However, there are few research reports on fabrics with waterproof, anti-fouling and breathable functions, resulting in significant defects in visible fabrics in applications. Summary of the invention

[0003] In view of this, the present application provides a method for preparing a multifunctional high-visibility fabric, which not only meets the requirements of fluorescent color and wet processing fastness, but also has good waterproof, anti-fouling and moisture permeability functions, and is more applicable.

[0004] Specifically, the present application is implemented through the following scheme: A method for preparing a multifunctional high-visibility fabric, taking a polyester-cotton blended fabric as a processing object, and performing the following processing: Step 1, preparing a modifier by adding sodium hydroxide, cellulose complex enzyme, and penetrant into water, immersing the polyester-cotton blended fabric in the modifier, washing with water until neutral, and drying to obtain a modified fabric; Step 2: using 0.5-10% guar gum and 0.2-1% nano-silica as monomers, adding 1-5% acrylic acid, 1-5% butyl acrylate, 1-5% sodium dodecyl sulfate and water, stirring to obtain a monomer emulsion; adding 0.5-1% initiator to the monomer emulsion to react to obtain a polyacrylate emulsion, adjusting the pH of the emulsion to 6-7 after the reaction is completed, and adding 1-10% sodium dodecylbenzene sulfonate, 2-20% acryloxypropyl caged polysilsesquioxane and the remaining emulsifier, stirring to react at room temperature, filtering, and centrifuging to remove impurities to obtain a fluorine-free waterproof and antifouling finishing agent; Step three, mixing the pigment, persimmon paint, the fluorine-free waterproof and antifouling finishing agent obtained in step two and deionized water to obtain a slurry, applying the obtained slurry on the modified fabric obtained in step one, and performing ultraviolet curing to obtain a finished product.

[0005] The above scheme first performs modification pretreatment on the polyester-cotton blended fabric, then applies a slurry formed by a finishing agent, a pigment, and a persimmon paint, completes the coating by a single-sided printing method, and then bakes to obtain a finished product. The obtained product is a high-visibility fabric with fluorescent properties, washability, and durability. The fabric not only meets the required fluorescent color and wet fastness, but also has good waterproof, anti-fouling, and moisture permeability functions.

[0006] Further, as a preference: In step one, The mass percentages of the components in the modifier are as follows: Sodium hydroxide concentration: 1-10 g / L, Cellulose complex enzyme concentration: 1-5 g / L, Osmotic agent concentration: 0.5-2 g / L, Bath ratio 1:50.

[0007] The immersion treatment is carried out at a temperature of 40 to 60° C. and for a duration of 1 to 3 hours.

[0008] The drying temperature is 60-80° C., and the drying time is 20-30 minutes.

[0009] In step 2, The mass ratio of guar gum to nano silicon dioxide is 4:1 to 1:4.

[0010] The reaction conditions of the polyacrylate emulsion are: under nitrogen protection, react at 70-90°C for 3-5 hours.

[0011] In step three, In the slurry, the mass percentage of each component is: Pigment: 1-5%, Persimmon paint: 1-12%, Fluorine-free water-repellent and antifouling finishing agent: 10-30%, The balance was deionized water.

[0012] The pigment is either fluorescent yellow or fluorescent orange.

[0013] The pre-baking temperature after coating is 60-80° C. and the duration is 10-30 minutes.

[0014] UV curing treatment: intensity 40~45.0W / m 2 , temperature 20 ~ 45 ℃, duration 1 ~ 5h.

[0015] The fabric obtained by the above scheme not only has good waterproof and stain-proof properties, but also maintains the original good hygroscopicity and excellent washability of the polyester-cotton blended fabric; after coating and finishing, the fabric is obtained by low-temperature ultraviolet curing treatment. This process uses a relatively low temperature to achieve good waterproof performance, avoids the influence of high-temperature baking on the fluorescent properties and feel of the fabric, saves energy, and has little effect on the fluorescent properties, feel and color change of the fabric. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0017] Figure 1 Scanning electron micrographs of fabrics before and after finishing; Figure 2 Infrared spectra of fabric before and after finishing. DETAILED DESCRIPTION

[0018] In order to make the technical problems, technical solutions and beneficial effects to be solved by this application clearer, the technical solutions in the embodiments of this application will be further described in detail below in conjunction with the drawings in the embodiments of this application. It should be understood that the specific embodiments described herein are only used to explain this application and are not used to limit the technical solutions of this application. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0019] Test method: Fluorescence performance evaluation method: refer to GB 20653-2006 "Occupational High Visibility Warning Clothing" method for evaluation, and use Datacolor 600 computer colorimeter to measure with D65 light source and 2° viewing angle. Fluorescent yellow color should be within the color range specified by the national standard, and its minimum brightness coefficient β should exceed 0.70.

[0020] The waterproof test is carried out according to the "Testing and Evaluation of Waterproof Performance of Textiles - Water Dipping Method" (GB / T 4745-2012) to test the waterproof performance of textiles. The higher the grade, the better the performance.

[0021] The stain resistance is tested in accordance with the "Testing and Evaluation of Anti-Stain Performance of Textiles Part 1: Stain Resistance" (GB / T30159.1-2013). In addition to the high-salt diluted soy sauce stains specified in the standard, corn oil is used for the same test. The higher the grade, the better the performance.

[0022] Water absorption rate: Place the sample in a container filled with grade 3 water. The sample will naturally sink after absorbing water. Take it out after being completely soaked for 5 minutes and hang it vertically and naturally. The water in the sample will drip naturally. When the sample stops dripping, weigh the sample immediately, accurate to 0.001 g. Repeat three times and take the average value. The water absorption rate calculation formula is: A(%)=(m-m0) / m0×100.

[0023] Among them, A is the water absorption rate, m0 is the original mass of the sample, and m is the mass of the sample after being completely soaked.

[0024] Water drop diffusion: After the sample has been equilibrated in standard atmosphere for 24 hours, drop 0.2 mL of water vertically at 90° on the sample and record the time required for the water drop to completely diffuse from the contact with the sample surface to an accuracy of 0.1 s. Repeat 5 times and calculate the average value.

[0025] Textile color fastness: Test the color transfer of textiles in dry and wet states according to the standard "Textiles - Tests for Color Fastness - Color Fastness to Rubbing" (GB / T 3920-2024). Test the color retention of textiles under washing conditions according to the standard "Textiles - Tests for Color Fastness - Color Fastness to Water" (GB / T 5713-2013).

[0026] The hand feel test was conducted with reference to the AATCC EP5-2011 fabric hand feel evaluation procedure. The treated samples were compared with the original samples, and the feeling level was described according to the change in hand feel. Level 1 was no different feeling; Level 2 was a slight different feeling; Level 3 was a moderate different feeling; and Level 4 was a significant difference.

[0027] Example 1

[0028] The preparation method of the multifunctional high-visibility fabric of this embodiment is as follows: Step 1: Modification treatment: The modifier was prepared by adding 5g / L sodium hydroxide, 4g / L cellulose complex enzyme (model Celluclast), 1g / L penetrant JFC and deionized water. The 65 / 35 polyester-cotton blended fabric was immersed in the modifier, immersed at 50℃ for 1h, and the bath ratio was 1:50. After the immersion, the fabric was fully washed three times with deionized water until neutral, and dried at 80℃ for 30min to obtain the modified fabric.

[0029] Step 2: preparing the finishing agent: 1) Take 3.5g guar gum, 6.5g sodium dodecyl sulfate and 0.8g nano-silica as monomers, add 3.2g butyl acrylate, 7.4g acrylic acid and 70mL deionized water, stir and dissolve thoroughly, and stir at 900 rpm for 30min to obtain a pre-emulsified monomer emulsion.

[0030] 2) The monomer emulsion was added into a reactor, and 1.7 g of potassium persulfate was added as an initiator. Under nitrogen protection, the polymerization reaction was carried out at 70° C. for 4 h to obtain a polyacrylate emulsion.

[0031] 3) After the polymerization reaction is completed, the pH value of the emulsion is adjusted to 7, 1.5 g of sodium dodecylbenzene sulfonate, 1.5 g of Tween 80 and 15 g of acryloxypropyl caged polysilsesquioxane are added, and the mixture is stirred for 3 h at room temperature. Finally, the solid impurities in the emulsion are removed by filtration and centrifugation to obtain a fluorine-free waterproof and antifouling finishing agent.

[0032] Step 3: Single-sided scraping and finishing: 2% fluorescent yellow, 8% persimmon paint, 0.8% nano-silicon dioxide, 30% fluorine-free waterproof and antifouling finishing agent, and 59.2% deionized water were stirred and mixed to obtain a slurry. The slurry was applied once on the modified fabric obtained in step 1 using an 80-mesh screen frame and a rubber scraper. The treated fabric was placed in an oven at 80°C and dried for 20 minutes. Then, it was dried at 40°C and 45.0W / m 2 After 5 hours of UV curing treatment, a waterproof, anti-fouling, moisture-absorbent, multifunctional high-visibility fabric was obtained.

[0033] Figure 1 The electron scanning microscope pictures of the fabric before and after finishing: the surface of the unfinished fabric is smooth, no other substances are adhered, and the yarns are arranged loosely; the yarns of the finished fabric are covered with a layer of material, and there are granular substances, and the yarn surface is rougher than the unfinished fabric. This shows that the finishing agent is wrapped on the yarn surface, and the nano-silicon dioxide gathers on the yarn surface to form a micro-nano rough structure, which increases the water contact angle, thereby improving the waterproof and anti-fouling ability of the fabric.

[0034] Figure 2 Infrared spectra of the fabric before and after finishing: The original fabric without finishing has an infrared spectrum of 3336 cm -1 A broad and strong absorption peak appears in the cellulose, which is the characteristic of hydroxyl groups in cellulose, at 1650 cm -1 There is a moderate absorption peak, which is the bending vibration characteristic of the hydroxyl group in cellulose. For the finished fabric, the absorption peaks of these two places are obviously weakened or shifted. -1 A new absorption peak initially appeared, which is a typical characteristic of ester carbonyl; at 2322 cm -1 The new absorption peak at 1271 cm -1 The new absorption peak at is the Si-O bond (Si-O) stretching absorption peak, which indicates that the hydroxyl groups on the fabric are blocked or reacted by the finishing agent after finishing, and the number is reduced. At the same time, a new siloxane structure appears, and the finishing agent reacts with the fabric and exists on the fabric.

[0035] The performance of the obtained fabric was tested, and the water absorption rate was 198%, the water drop diffusion was 10.2s, the breaking strength was 165N, the brightness coefficient β was 0.73, and the waterproofness and stain resistance both reached level 5.

[0036] Comparative Example 1

[0037] The configuration of this comparative example is the same as that of Example 1, except that the polyester-cotton blended fabric is not subjected to modification treatment before the single-sided scraping and printing finishing.

[0038] Table 1: Effect of modification on finishing effect .

[0039] The purpose of modifying the fabric by using sodium hydroxide and cellulase is to remove the impurities and oil stains remaining on the fabric and improve the hydrophilicity of the fabric and the ability to bind with the finishing agent. Therefore, compared with Comparative Example 1, under the same conditions, Example 1 has improvements in water absorption, drip diffusion, brightness coefficient and waterproofness, and slightly reduces the breaking strength.

[0040] Comparative Example 2

[0041] The configuration of this comparative example is the same as that of Example 1, except that: in step 3, no persimmon paint is added, and only a commercially available fluorine-free finishing agent (RUCO-DRY ECO PLUS) is added.

[0042] Table 2: Effect of finishing agents .

[0043] Comparative Example 2 did not add the homemade waterproof finishing agent and persimmon paint. Compared with Example 1, its brightness coefficient was lower and did not meet the high-visibility national standard requirements. The waterproofness, stain resistance, color fastness to washing and color fastness to rubbing were all lower than that of Example 1. The addition of persimmon paint is conducive to the uniform dispersion of the pigment in the emulsion, and has the effect of a cross-linking agent, synergistically acting on the fabric with the homemade finishing agent, improving the fluorescence performance and waterproofness of the fabric, and the fabric has good color fastness.

[0044] Example 2

[0045] The configuration of this embodiment is the same as that of embodiment 1, except that the concentrations of sodium hydroxide and cellulose complex enzyme are different, as shown in Table 3.

[0046] Table 3: Effects of different mass ratios of sodium hydroxide and cellulose complex enzyme on fabric properties .

[0047] Table 3 shows that as the concentration of sodium hydroxide increases, the water absorption rate of the modified fabric continues to increase; as the proportion of cellulose complex enzyme increases, the drip diffusivity continues to increase. Sodium hydroxide treatment has an etching effect on the polyester component and can cause the cotton fiber component to swell, which together improves the hydrophilicity of the fabric. It synergizes with cellulose complex enzyme to remove hydrophobic impurities on the surface of the fabric and reduce the crystallinity of the fibers in the fabric. The concentration of sodium hydroxide and cellulose complex enzyme should be controlled within the range of 5g / L and 4g / L. At this time, the water absorption rate and drip diffusivity are good, and the breaking strength meets the use requirements.

[0048] Example 3

[0049] The configuration of this embodiment is the same as that of embodiment 1, except that the modification temperature is replaced from 50°C to 40°C, 45°C, 55°C, and 60°C, respectively, as shown in Table 4.

[0050] Table 4: Effect of modification temperature on fabric properties .

[0051] It can be seen from Table 4 that the modification temperature should not be too high. When the treatment temperature exceeds 50°C, the strength of the fabric will decrease, affecting its wearing performance. The modification temperature is preferably controlled at 50-55°C.

[0052] Example 4

[0053] The configuration of this embodiment is the same as that of Embodiment 1, except that the mass percentage of persimmon paint is replaced by 1%, 2%, 5%, and 10% from 8%, respectively, as shown in Table 5.

[0054] Table 5: Effect of persimmon lacquer mass percentage on fabric properties .

[0055] Table 5 shows that as the concentration of persimmon lacquer increases, the brightness coefficient of the functional fabric continues to increase; when the mass percentage of persimmon lacquer is 8%, it can meet the requirements of high-visibility fabrics, and has good waterproof and stain resistance, and the feel does not change; however, when the mass percentage of persimmon lacquer exceeds 8%, the brightness coefficient decreases, the fluorescence performance of the fabric deteriorates, and the feel of the fabric deteriorates. Persimmon lacquer is a natural high molecular polymer that can form a film under certain conditions and has good waterproof properties. Persimmon lacquer contains polar groups such as hydroxyl groups. Adding an appropriate amount can improve the dispersion uniformity of fluorescent pigments and improve the fluorescence performance of fabrics. However, when the concentration is too high, the persimmon lacquer polymerizes into a polymer, which affects the fluorescence performance of the fabric and makes the fabric feel harder. Therefore, the addition amount of persimmon lacquer should be controlled at 8%.

[0056] Example 5

[0057] The configuration of this embodiment is the same as that of embodiment 1, except that the added mass percentage of the fluorine-free water-repellent and antifouling finishing agent is replaced from 30% to 5%, 10%, 20%, and 50%, respectively, as shown in Table 6.

[0058] Table 6: Effect of modification temperature on fabric properties .

[0059] It can be seen from Table 6 that with the increase in the amount of fluorine-free waterproof and antifouling finishing agent, the waterproofness and stain resistance of the fabric are significantly improved, and the fluorescence performance (brightness coefficient β) does not change much; guar gum is a derivative of a natural high molecular polymer, which has film-forming and adhesion properties similar to those of large molecular polymers. The hydroxyl and hydrogen bonds in its structure can produce good binding force with the fabric and have good water repellent and antifouling properties. The addition of nano-titanium dioxide can form a raised microstructure on the surface of the fabric, further improving the waterproof performance. When the amount of fluorine-free waterproof and antifouling finishing agent is greater than 30%, the fluorescence performance of the fabric decreases. This may be because the surface coating of the fabric is thicker, reducing its flexibility and fluorescence performance. Therefore, the amount of fluorine-free waterproof and antifouling finishing agent added to the slurry should be controlled at 10-30%, and 20-30% is preferred.

[0060] Example 6

[0061] The configuration of this embodiment is the same as that of embodiment 1, except that the UV curing temperature is replaced from 40°C to 20°C, 30°C, 35°C, and 45°C, respectively, as shown in Table 7, compared with the conventional high temperature baking process (150°C, 1 min).

[0062] Table 7: Effect of UV curing temperature on fabric properties .

[0063] It can be seen from Table 7 that: with the increase of curing temperature, the waterproofness and stain resistance of the fabric gradually improve, and the fluorescence performance does not change much; compared with the traditional baking process, the use of ultraviolet curing treatment can achieve better waterproof performance at a relatively low temperature, avoiding the influence of high-temperature baking on the fluorescence performance and feel of the fabric, and saving energy.

[0064] The above-mentioned embodiments only express several feasible implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention, and the embodiments are not used to limit the scope of protection in the claims of the present invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and all equivalent implementations or changes that do not depart from the present invention should be included in the technology of the present invention.

Claims

1. A method for preparing a multifunctional high-visibility fabric, characterized in that: Take polyester-cotton blended fabric as the treatment object and carry out the following treatment: Step 1: preparing a modifier by adding sodium hydroxide, cellulose complex enzyme, and penetrant into water, immersing the polyester-cotton blended fabric in the modifier, washing with water until neutral, and drying; Step 2: using 0.5-10% guar gum and 0.2-1% nano-silica as monomers, adding 1-5% acrylic acid, 1-5% butyl acrylate, 1-5% sodium dodecyl sulfate and water, stirring to obtain a monomer emulsion; adding 0.5-1% initiator to the monomer emulsion to react to obtain a polyacrylate emulsion, adjusting the pH of the emulsion to 6-7 after the reaction is completed, and adding 1-10% sodium dodecylbenzene sulfonate, 2-20% acryloxypropyl caged polysilsesquioxane and an emulsifier, stirring to react at room temperature, filtering, and centrifuging to remove impurities to obtain a fluorine-free waterproof and antifouling finishing agent; Step three, mixing the pigment, persimmon paint, the fluorine-free waterproof and antifouling finishing agent obtained in step two and deionized water to obtain a slurry, applying the obtained slurry on the fabric obtained by drying in step one, and performing ultraviolet curing to obtain a finished product.

2. The method for preparing a multifunctional high-visibility fabric according to claim 1, characterized in that: The mass percentages of the components in the modifier are as follows: Sodium hydroxide concentration: 1-10 g / L, Cellulose complex enzyme concentration: 1-5 g / L, Osmotic agent concentration: 0.5-2 g / L, Bath ratio 1:

50.

3. A method for preparing a multifunctional high-visibility fabric according to claim 1 or 2, characterized in that: The concentration ratio of sodium hydroxide to cellulose complex enzyme is 2 to 1:

1.

4. The method for preparing a multifunctional high-visibility fabric according to claim 1, characterized in that: In step 1, the immersion treatment temperature is 40-60° C. and the duration is 1-3 hours.

5. The method for preparing a multifunctional high-visibility fabric according to claim 1, characterized in that: In step 1, the drying temperature is 60-80° C. and the drying time is 20-30 minutes.

6. The method for preparing a multifunctional high-visibility fabric according to claim 1, characterized in that: In step 2, the mass ratio of guar gum to nano silicon dioxide is 4:1 to 1:

4.

7. The method for preparing a multifunctional high-visibility fabric according to claim 1, characterized in that: In step 2, under nitrogen protection, the reaction is carried out at 70-90° C. for 3-5 hours to obtain a polyacrylate emulsion.

8. The method for preparing a multifunctional high-visibility fabric according to claim 1, characterized in that: In the slurry, the mass percentage of each component is: Pigment: 1-5%, Persimmon paint: 1-12%, Fluorine-free water-repellent and antifouling finishing agent: 10-30%, The balance was deionized water.

9. The method for preparing a multifunctional high-visibility fabric according to claim 1, characterized in that: The ultraviolet curing intensity is 40 to 45.0 W / m 2 , temperature 20 ~ 45 ℃, duration 1 ~ 5h.

10. The method for preparing a multifunctional high-visibility fabric according to claim 1, characterized in that: After coating, pre-baking is performed at a temperature of 60 to 80°C. After pre-baking for 10 to 30 minutes, ultraviolet curing is performed.

Citation Information

Patent Citations

  • Environmentally-friendly desizing agent used for high-density polyester fabric and preparation method thereof

    CN105603710A

  • Persimmon dyeing method

    CN110656511A

  • Easy-to-clean finishing agent and method for preparing highly-visible easy-to-clean fabric by using easy-to-clean finishing agent

    CN117702483A